A case report of a bipolar disorder patient with severe lithium poisoning possibly induced by interaction between risperidone, telmisartan, fluvoxamine and lithium - Yi Xin Cheng and Chee Ping Chong (Journal of Applied Pharmaceutical Science, 2013)
We describe a case of severe lithium poisoning possibly induced by multiple drugs interaction. A 45-year-old man with bipolar disorder was admitted with altered behavior and mental status. He was maintained on lithium for 20 years. Nine months ago, lithium dose was increased and risperidone was added. Telmisartan was prescribed around 25 days ago and he had mild tremor since then. Two days ago, fluvoxamine was initiated and he developed restlessness, agitation, insomnia and confusion after one dose. On admission, fluvoxamine, lithium, telmisartan and risperidone were discontinued. Abnormal findings were temporary ST depression, hyponatremia and high creatine kinase. He had fever since day 2 and was covered for meningoencephalitis and neuroleptic malignant syndrome. On the next day, his was comatose and treated for septic shock. On day 7, result of serum lithium taken on day 3 revealed severe toxicity (3.2 mEq/L). The lithium level was normalized after hemodialysis. He subsequently regained full Glasgow Coma Scale score and his toxicity completely resolved on day 16. Interactions of risperidone and telmisartan with lithium possibly precipitated the lithium toxicity. However, the onset of the toxicity suggested fluvoxamine as the major cause of poisoning. Clinicians should be aware of these potential drug interactions.
Keywords: Lithium toxicity, lithium poisoning, drug interactio